IMPROVEMENT OF CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS AFTER THE IMPLEMENTATION OF PROBLEM-BASED LEARNING - Elsa Safitri; Nur Asyiah; Aliet Noorhayati Sutisno (Jurnal Cakrawala Pendas, 2026)
Elementary school students’ critical thinking skills remain low because instruction tends to be teacher-centered and does not yet provide many opportunities to analyze contextual problems. This study aims to determine the improvement in students’ critical thinking skills following the implementation of the Problem-Based Learning model, supported by instructional videos, in the Natural and Social Sciences subject on the topic of “A Changing Earth.” The study employed a pre-experimental method with a one-group pretest-posttest design. The research participants consisted of 29 fifth-grade students selected using saturation sampling. Data were collected using open-ended tests based on higher-order thinking skills, as well as observation sheets assessing instructional implementation and critical thinking behaviors. Data analysis was conducted through normality tests, paired t-tests, calculations of normalized gains, and analysis of the percentage of observation results. The results showed that the students’ average scores increased from 30.17 on the pretest to 70.25 on the posttest. The paired t-test revealed a significant difference in critical thinking skills before and after instruction. The normalized gain of 0.5740 fell into the moderate category. The implementation of the learning process reached 82.5%, falling into the “good” category, while critical thinking behaviors improved from the “low” category to the “high” category. Improvements were observed across all indicators, particularly in providing simple explanations and drawing conclusions. Thus, the application of the Problem-Based Learning model, supported by instructional videos, led to an improvement in students’ critical thinking skills, although further reinforcement is still needed in the areas of providing more detailed explanations and formulating strategies and tactics.